Genes in the aetiology of oculocutaneous albinism in Sub-Saharan Africa and a possible role in tuberculosis susceptibility - Kerr, Robyn (My University, 2008)
ABSTRACT In southern Africa, oculocutaneous albinism (OCA) is the most common autosomal recessive disease amongst black Africans, occurring with a prevalence of approximately 1 in 3 900 individuals. OCA occurs in southern African Caucasoids with a frequency that reflects the European origins of this population, approximately 1 in 20-30 000. OCA type 1 is caused by mutations in the tyrosinase gene on chromosome 11q. Tyrosinase mutations occur in the Caucasoid population but are extremely rare in black Africans. OCA type 2 is caused by mutations in the P gene on chromosome 15q. P gene mutations occur in both the black and Caucasoid populations. A sub-type of OCA2 seen in black individuals, brown OCA (BOCA), is also caused by mutations at the P gene locus. A mutation screen was undertaken to identify disease-causing mutations in a group of OCA subjects from Sub-Saharan Africa. A common P gene mutation had been identified in the black population, a 2.7 kb intragenic deletion, accounting for 78% of P gene mutations in this group. No common tyrosinase mutations have been identified to date, in any population. A cohort of OCA subjects from South Africa, Lesotho, Zambia and the Central African Republic (CAR) were available for study in our laboratory. All subjects were screened for the 2.7 kb deletion mutation. Subjects homozygous for this mutation were excluded from further study. Subjects where one or two mutations remained to be identified were included in a mutation screen (63 blacks and 9 Caucasoids). Depending on the clinical categorisation of the type of albinism, subjects were screened for P gene mutations only (black OCA2) or were screened for P gene mutations and tyrosinase mutations (BOCA, unclassified black OCA and unclassified Caucasoid OCA). All 72 subjects were screened for P gene mutations and ten putative pathogenic mutations were identified. In the group of black OCA2 patients, four mutations which are likely to be pathogenic were found: A334V, 614delA, 683insT and 727insG. Mutations were identified in four individuals with an unusual hypopigmentation phenotype: E678K was found in the homozygous state in an individual from the CAR. A second individual was found to be a compound heterozygote for the I370T and the L688F mutations. A third individual was found to be heterozygous for the I370T mutation. Three P gene mutations were found in the Caucasoid sample: IVS 14-2 (a→g), V350M and P743L. No further mutations were identified in the BOCA sample. The P gene screen comprised 72 subjects, but 40 were heterozygous for the 2.7 kb deletion, therefore (144 minus 40 alleles) 104 alleles remained to be identified. Identification of 12/104 alleles means that a further 11.5% of the unknown P gene mutations are now accounted for. Thirty three of the 72 subjects were included in a further mutation screen – at the tyrosinase locus. Four mutations were identified, all in the Caucasoid group. Compound heterozygosity was shown in two individuals, one carrying the mutations, E294K and A490D and the other, P431T and T373K. Following mutation analysis of the P gene, it was apparent that a proportion of mutations did not lie in the coding region of the gene and it was proposed that some of the remaning unidentified mutations might be found in the 5’control or promoter region of the gene. At that time, sequence data for the region upstream of the P gene was not known, and so an attempt was made to clone the 5’region of the P gene. Two approaches were adopted – a bacterial artificial chromosome (BAC) known to contain this region was subcloned; and secondly, an inverse PCR experiment was undertaken. Neither experiment was successful in generating P gene promoter sequence. Variation at the P locus was investigated in a second context. This region of chromosome 15q was implicated as a host susceptibility locus for the infectious disease, tuberculosis (TB). A case-control study was undertaken to compare the frequencies of five intragenic, polymorphic markers in the P gene: the 2.7 kb deletion, the R305W polymorphism and the microsatellite markers, D15S1533, D15S1536 and D15S1537, between a group of black South African TB patients from Gauteng and healthy community controls and between a group of mixed-ancestry (Coloured) TB patients and healthy controls from the Western Cape region. Presence or absence of the 2.7 kb deletion mutation does not appear to influence susceptibility to TB in either the black or Coloured population samples studied here. The W allele of the R305W polymorphism is significantly (p<0.05) more common in the black patient group than in the black control group, suggesting it may be in linkage disequilibrium with a disease susceptibility allele. Microsatellite marker analysis showed that, in the black population, allele 18 at the D15S1533 locus is significantly (p<0.05) associated with susceptibility to TB. In the Cape Coloured population, alleles 20 and 27 at the D15S1533 locus, allele 12 at the D15S1536 locus and allele 16 at the D15S1537 locus are over represented in the patient group suggesting they may be markers for increased susceptibility to TB. Further, in the Coloured population alleles 12, 13 and 15 at the D15S1537 locus showed significant (p<0.05) association with normal controls and may be in linkage disequilibrium with protective or resistance alleles. The results of this study support the proposal of a TB susceptibility locus on chromosome 15q. OCA-causing mutations have been identified, but many remain elusive. Further characterisation of this region will give us a better understanding of the biological consequences of variation both within and around the P locus.
Keywords: oculocutaneous albinism; tuberculosis susceptibility